A differential expression of uncoupling protein-2 associates with renal damage in stroke-resistant spontaneously hypertensive rat/stroke-prone spontaneously hypertensive rat-derived stroke congenic lines. Issue 9 (September 2017) - Rubattu, Speranza; Cotugno, Maria; Bianchi, Franca; Sironi, Luigi; Gelosa, Paolo; Stanzione, Rosita; Forte, Maurizio; De Sanctis, Claudia; Madonna, Michele; Marchitti, Simona; Pignieri, Alice; Sciarretta, Sebastiano; et al.
Abstract : Objectives: Uncoupling protein-2 (UCP2), a mitochondrial anion transporter involved in mitochondrial uncoupling, limiting reactive oxygen species formation, is significantly downregulated in kidneys of high-salt-fed stroke-prone spontaneously hypertensive rat (SHRSP), where it associates with increased renal damage occurrence. Methods: We aimed at establishing whether UCP2 differential expression associates with renal damage in two stroke-resistant spontaneously hypertensive rat (SHRSR)/SHRSP-derived stroke congenic lines. For this purpose, SHRSR, SHRSP, and two reciprocal stroke congenic lines carrying the (D1Rat134-Mt1pa) segment of chromosome 1 were fed with Japanese style diet for 8 weeks. At 4, 6, and 8 weeks of Japanese diet, kidneys were removed and analyzed for UCP2 gene and protein expression [ UCP2 maps within (D1Rat134-Mt1pa)]; nuclear factor kappa-light-chain-enhancer of activated B cells protein expression; oxidized total protein levels; mitochondrial function; gene expression of cubulin, megalin, and nephrin. At 6 and 8 weeks of Japanese diet, histological damage and percentage of high molecular weight urinary proteins excretion were assessed. Results: Introgression of UCP2 in the SHRSP configuration within the SHRSR genome led to UCP2 downregulation upon Japanese diet, as compared with the SHRSR, with significantly reduced ATP levels, increased rate of inflammation, oxidative stress, renal damage, and excretion of high molecular weight proteins. The opposite phenomena were observed in the reciprocal congenic line, compared with the SHRSP. In vitro, high-NaCl medium led to UCP2 downregulation, increased apoptosis/necrosis, and reduced viability in primary renal proximal tubular epithelial cells isolated from SHRSP. Exposure of the SHRSP/proximal tubular epithelial cells to recombinant UCP2 rescued the high-salt-dependent deleterious effects. Conclusion: A differential UCP2 expression associates with different degree of renal damage upon Japanese diet in two SHRSR/SHRSP-derived stroke congenic lines through modulation of mitochondrial function, inflammation, and oxidative stress.